The Development of Indonesian Open Access Journal Publishing: an Analysis of the Impact of Government Policy in Enhancing Indonesian Scholarly Communication - White, Hollie; Kiramang, Khaeruddin (2018)
Description: This paper evaluates the current state of scholarly Open Access journal publishing in Indonesia, including the alignment between Government policy and the practice of research institutions and individuals. This study uses qualitative content analysis and descriptive statistical techniques to analyse the relationships and impact of Indonesian government regulations on the number of Indonesian journals listed in DOAJ. Selected regulations were analysed using qualitative content analysis techniques and classified into three categories: quantity, quality, and visibility. The results indicate that the regulations from 2014 to 2017 related to visibility enhancement have had the most impact on proliferation of Indonesian OA journal publishing. The limitation of this research is the inability to identify and evaluate other factors that may influence the growth of Indonesian Open Access journals. However, the results provide an important example of the impact of government regulations on the potential growth of Open Access journal publishing in developing countries. This research provides practical advice to policy makers and research institutions in developing countries on how to optimise the benefits of Open Access journal publishing.